Tingkat kematian Anopheles vagus yang terpapar Insektisida permethrin 2% (w/w) di dalam Serat benang kelambu - Yahya Yahya; Endang Puji Astuti (Loka Litbang Kesehatan Pangandaran, 2013)
Various efforts to control mosquito-borne diseases have been done i.e the use of insecticide-treated nets (ITN). The aim of this study was to determine the insecticide permethrin in the nets to control Anopheles vagus mosquito that were widely distributed in the village of Tanjung Seleman, Muara Enim district based upon age and frequency of laundering. An experimental research using a complete randomized design was conducted in April-December 2010. Data regarding the effectiveness of permethrin against Anopheles, were collected through biossay test (WHO cone test) with contact method. Entomology bioassay data is the average of mosquito mortality for nets that given in 2006 was 66.5%, for the nets in 2007 the mortality rate reached 67.3%, and for mosquito nets in 2008 the mortality rate reached 67.5%. It shows that there were differences effect on mortality of An. vagus which exposed to mosquito net that has never been washed with the washing 1-3 times or more, while the mortality of mosquito that exposed to different age of nets shows no significantly difference. Percentage of An. vagus mortality that exposed by permethrin insectiside is still high